2001
DOI: 10.1002/1098-2736(200102)38:2<137::aid-tea1001>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Professional development and reform in science education: The role of teachers' practical knowledge

Abstract: In this article, professional development in the context of the current reforms in science education is discussed from the perspective of developing teachers' practical knowledge. It is argued that reform efforts in the past have often been unsuccessful because they failed to take teachers' existing knowledge, beliefs, and attitudes into account. Teachers' practical knowledge is conceptualized as actionoriented and person-bound. As it is constructed by teachers in the context of their work, practical knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
298
1
41

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 668 publications
(371 citation statements)
references
References 73 publications
9
298
1
41
Order By: Relevance
“…Along with general research on teachers' beliefs, there are also studies of teachers' beliefs about mathematics and science teaching (e.g., Cross, 2009;Enochs & Riggs, 1990;Van Driel, Beijaard, & Verloop, 2001). For example, using the Science Teaching Efficacy Belief Inventory (STEBI, Enochs & Riggs, 1990), Angle and Moseley (2009) found that teachers' outcome expectancies were related to higher levels of proficiency on an end-of-year biology exam.…”
Section: Teacher Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Along with general research on teachers' beliefs, there are also studies of teachers' beliefs about mathematics and science teaching (e.g., Cross, 2009;Enochs & Riggs, 1990;Van Driel, Beijaard, & Verloop, 2001). For example, using the Science Teaching Efficacy Belief Inventory (STEBI, Enochs & Riggs, 1990), Angle and Moseley (2009) found that teachers' outcome expectancies were related to higher levels of proficiency on an end-of-year biology exam.…”
Section: Teacher Efficacymentioning
confidence: 99%
“…For example, Cross (2009) reports an example of a teacher who thought that more constructivist student-centered strategies were important in geometry, but not in algebra. Van Driel et al (2001) report that teachers often affirm constructivist and reform beliefs, but tend to still teach in more traditional ways. The EYE module implementation depends upon the teachers using student-centered reform based practices to implement the modules.…”
Section: Teacher Efficacymentioning
confidence: 99%
“…While the lack of interest in science often manifests itself during secondary school when young people must choose the subjects they will study, most students have already excluded the choice of scientific or technological subjects long before, i.e., during their years in primary school (Osborne & Dillon, 2008, Tai, Qi Liu, Maltese, & Fan, 2006Young & Kellogg, 1993). Science education should therefore pay explicit attention to improving students' interest in and attitudes toward science, and this should take place beginning at the primary school level (Haney, Czerniak, & Lumpe, 1996;Tobin, Tippins, & Gallard, 1994;Van Driel, Beijaard, & Verloop, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the attitudes of primary teachers toward science have indicated that teachers with less positive attitudes share a number of characteristics. They have lower confidence and self-efficacy beliefs about teaching science (Skamp, 1991;Tosun, 2000;Yates & Goodrum, 1990); they spend less time discussing and teaching these topics in their classrooms (Goodrum, Hackling, & Rennie, 2001;Harlen & Holroyd, 1997); they rely more on standardized methods and top-down instruction (Appleton & Kindt, 1999;Harlen & Holroyd, 1997;Jarvis & Pell, 2004;Plonczak, 2008); and they are less able to stimulate the attitudes of their students (Harlen & Holroyd, 1997;Jarvis & Pell, 2004;Osborne et al, 2003;Van Driel et al, 2001;Weinburgh, 2007). On the positive side, research has shown that when teachers gain greater confidence and self-efficacy and a more positive attitude through continuing education efforts, they subsequently teach science in a better manner and are able to improve the attitudes of their students in this area (Osborne & Dillon, 2008;Osborne et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Les travaux de Schechter et Ganon (2012) vont dans le même sens et précisent qu'une CA qui valorise un leadership distribué permet aux participants de contribuer à l'agenda et de se sentir valorisés. Il ne suffit pas de remettre un curriculum révisé entre les mains des enseignants pour qu'ils intègrent les nouveaux contenus ou approches (Van Driel, Beijaard et Verloop, 2001). Pour participer à l'amélioration de leurs pratiques pédagogiques et décider de l'orientation à suivre pour y parvenir, les enseignants ont besoin d'être soutenus dans leur milieu.…”
Section: Problème Objectif Et Questions De Rechercheunclassified